Quantifying the Sheath Impedance of the Electric Double Probe Instrument on the Van Allen Probes. Issue 5 (6th May 2022) - Hartley, D. P.; Christopher, I. W.; Kletzing, C. A.; Kurth, W. S.; Santolik, O.; Kolmasova, I.; Wygant, J. R.; Bonnell, J. W.
Abstract: Spherical double probe electric field sensors become electrically coupled to magnetospheric plasma during operation, leading to an instrument response that varies with the local plasma environment. Here, a method is developed for determining this variable coupling impedance for each measurement direction by using periods of favorable boom, wave, and magnetic field geometry. Comparing electric field complex amplitudes between 30 Hz and 10 kHz observed along each boom direction to those predicted from simultaneous magnetic field measurements and cold plasma theory allows for the amplitude and phase response of the instrument to be quantified over the full range of plasma densities encountered on‐orbit. A sheath model is developed to describe how the sheath resistance, sheath capacitance, and relative effective length vary as a function of plasma density. An additional empirical correction is also included to describe the phase response along the spin‐axis. The modeled sheath correction is subsequently tested for case studies of burst‐mode data and statistical analyses of survey‐mode data. It is demonstrated that the levels of agreement between observations and theoretical predictions based on Faraday's Law are substantially greater for the sheath corrected data than for uncorrected observations. Comparisons between observations with oppositely directed Poynting vector directions reveals that the sheath correction reconciles a bifurcated distribution in the uncorrected data to a single peak centered on agreement with Faraday's Law. A full sheath corrected EMFISIS L4 survey mode data set has been produced for final archive. Full details of the sheath correction are also provided for manual data correction. Key Points: Variable coupling impedance between the instrument and plasma has been quantified for the electric field measurements on Van Allen Probes Sheath correction is demonstrated to substantially improve agreement between data and theoretical predictions from Faraday's Law Sheath‐corrected EMFISIS L4 data set produced for archive. Full details are also provided to facilitate manual data corrections